Integration of Social Emotional Learning Competencies in Teaching and Learning: A Narrative Inquiry - Mishra, Somnath (NPRC Journal of Multidisciplinary Research, 2025)
The integration of Social Emotional Learning (SEL) competencies into teaching and learning practices holds significant promise for fostering holistic student development, particularly within the unique socio-cultural context of Nepali schools. This narrative inquiry delves into the lived experiences of educators in Nepal as they navigate the complexities of embedding SEL competencies into their daily classroom routines. Through in-depth interviews and reflective journal, this study aims to capture the authentic voices and professional journeys of basic level teachers. It explores how these educators interpret, adapt, and implement SEL frameworks, considering local cultural values, pedagogical traditions, and resource availability. The research has illuminated the successes achieved in promoting students’ self-awareness, self-management, social awareness, relationship skills, and responsible decision-making. The findings posit that effective SEL integration in Nepal is a dynamic, iterative process requiring context-specific professional development, collaborative support networks among educators, and a broader systemic commitment to valuing emotional intelligence alongside academic achievement. The narratives generated has offer invaluable insights for Nepali educators, policymakers, and educational researchers striving to cultivate more empathetic, resilient, and socially competent future generations.